P346 Psychosocial factors associated with chlamydia retesting among young people in the UK. (14th July 2019) - Mcdonagh, Lorraine; Hunt, Elizabeth; Naidoo, Carla; Saunders, John; Dunbar, Kevin; Amlot, Richard; Weston, Dale
Abstract : Background: Repeat chlamydia infections are common, and the risk of receiving complications increases with the number of lifetime infections. However, retesting rates in the UK remain low and interventions to increase retesting have had variable effects. In order to change behaviour (e.g., to increase retesting), behavioural-science theoretical models may help identify influential factors. One such model, the COM-B Model proposes behaviour results from an interaction between capability, opportunity and motivation. The aim of this study was to identify theoretically-based demographic and psychosocial factors associated with retesting behaviour and intentions to retest amongst those previously diagnosed with chlamydia. Methods: An online questionnaire was developed, based on a comprehensive literature review and expert and lay consultation. Participants were 263 young people (16–24 years) in the UK who had been diagnosed with chlamydia (via healthcare settings or online platforms). In addition to demographic questions, each measure was representative of COM-B components: susceptibility and severity, fear, stigma, shame, knowledge, social support, social norms, perceived advantages/disadvantages of retesting. Results: 35% had not retested, the most common reason for which was unawareness of the need to retest (31%). In those who had not retested, moral norms, injunctive norms, and STI knowledge significantly predicted intentions to retest (F[1, 53] =6.20, p=0.016, R 2 =0.45, Adj R 2 =0.42). Retesters were slightly older and more likely to have had other STIs. The most common location of retest was a sexual health clinic (57%), followed by general practice (14%) and online services (11%). Multivariable regression demonstrated that social norms (injunctive, descriptive, and moral) significantly predicted having retested (F[1, 171] =7.44, p=0.007, R 2 =0.12, AdjR 2 =0.10]. Conclusion: This research has identified potential targets for public health campaigns aimed at eliminating STIs. Specifically, future interventions should focus on social (e.g., social approval one expects from others for engaging in a responsible sexual health action) and psychological (awareness and education) to increase retesting rates. Disclosure: No significant relationships.